DESENVOLVIMENTO DE UMA BANCADA PARA TESTES DE VENTILADORES CENTRÍFUGOS - Hoffmann, Roger S.; Bortolaia, Luis A.; Fonseca, Simão P. G. d. S.; Ritter, Douglas; Valdiero, Antonio C.; Basso, Samuel (Salão do Conhecimento, 2013)
Resumo